Multilocus genotyping of Giardia duodenalis in captive non-human primates in Sichuan and Guizhou provinces, Southwestern China. - Zhijun Zhong; Yinan Tian; Wei Li; Xiangming Huang; Lei Deng; Suizhong Cao; Yi Geng; Hualin Fu; Liuhong Shen; Haifeng Liu; Guangneng Peng (PLoS ONE)
Giardia duodenalis is a common human and animal pathogen. It has been increasingly reported in wild and captive non-human primates (NHPs) in recent years. However, multilocus genotyping information for G. duodenalis infecting NHPs in southwestern China is limited. In the present study, the prevalence and multilocus genotypes (MLGs) of G. duodenalis in captive NHPs in southwestern China were determined. We examined 207 fecal samples from NHPs in Sichuan and Guizhou provinces, and 16 specimens were positive for G. duodenalis. The overall infection rate was 7.7%, and only assemblage B was identified. G. duodenalis was detect positive in northern white-cheeked gibbon (14/36, 38.9%), crab-eating macaque (1/60, 1.7%) and rhesus macaques (1/101, 0.9%). Multilocus sequence typing based on beta-giardin (bg), triose phosphate isomerase (tpi) and glutamate dehydrogenase (gdh) revealed nine different assemblage B MLGs (five known genotypes and four novel genotypes). Based on a phylogenetic analysis, one potentially zoonotic genotype of MLG SW7 was identified in a northern white-cheeked gibbon. A high degree of genetic diversity within assemblage B was observed in captive northern white-cheeked gibbons in Southwestern China, including a potentially zoonotic genotype, MLG SW7. To the best of our knowledge, this is the first report using a MLGs approach to identify G. duodenalis in captive NHPs in Southwestern China.